Using Video in Urban Elementary Professional Development to Support Digital Media Arts Integration. Issue 2 (3rd April 2017) - Woodard, Rebecca; Machado, Emily
Abstract: Using ethnographic methods, this article looks closely at how a team of first-grade teachers and digital media artists in an urban elementary school used video in innovative ways during professional development over the course of one year. Extending a body of literature that primarily documents how video can be used as a tool in professional development to develop pedagogical knowledge and support reflective practice, this article documents how teachers in this partnership also consumed, connected through, and created videos to deepen digital media content knowledge and showcase their teaching and learning with a broader audience as part of a school-wide culture that attempted to create a "new ethos" (Lankshear & Knobel, 2007 ) of digital media arts mindsets.